Yttrium Oxide Nanoparticles Prepared by Heat Treatment of Cathodically Grown Yttrium Hydroxide. (17th November 2011) - Aghazadeh, Mustafa; Ghaemi, Mehdi; Nozad Golikand, Ahmad; Yousefi, Taher; Jangju, Esmaeil
Abstract : An easy two-step synthetic route is reported for the manufacture of yttrium oxide nanoparticles utilizing aqueous yttrium nitrate solution. In the first step, yttrium hydroxide precursor was grown on stainless steel electrode using a simple cathodic electrodeposition at room temperature. The subsequent second step includes the thermal decomposition of yttrium hydroxide powder at different temperatures for two hours. The synthesized products were characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetery (DSC), FT-IR and Raman spectroscopy. Results showed that the as-deposited Y(OH)3 is composed of nanoparticles with grain size of approximately 40–50 nm. Cubic-structured Y2 O3 phase with a porous morphology was finally formed when temperature was raised to 600°C. Results suggested that the final oxide nanoparticles are crystalline and consist only of yttrium oxide phase forming agglomerates of many primary particles with average diameter around 30 nm.